Rich dad poor dad : what the rich teach their kids about money-that the poor and middle class do not - Kiyosaki, Robert . (Scottsdale : Plata Publishing, 2017)
Taking to heart the message that the poor and middle class work for money, but the rich have money work for them, the author lays out a financial philosophy based on the principle that income-generating assets always provide healthier bottom-line results.
Keywords: Finance, Personal; Investments; Rich people